Developing emergent literacy in infant schools: a laboratory experience for the construction of the written language - Francesca Anello (Firenze University Press, 2017)
Research, including the educational neuroscience, has highlighted the close relationship between emerging literacy and subsequent learning of reading and writing. Early verification of symbolic and linguistic skills is essential to support the development, and recovery strategies are to be prepared in case of early signs of difficulty. In some infant schools in the Palermo area we carried out a laboratory of the last 45 hours, according to a specific methodological setting, with a dual aim: a) developing the emerging areas of literacy in preschool, b) providing teachers with an objective approach to detect in children reading and writing readiness. The study investigated phonological, lexical and pragmatic skills. We verified if an integrated curriculum based on storytelling could improve construction of the oral and written language, and phonological awareness in five-year old children. Although the findings concern only one experimental situation, the results showed the following a prepared educational programme produced an appreciable increasing of the individual performances.   Sviluppare l'alfabetizzazione emergente nella scuola dell'infanzia: un'esperienza laboratoriale per la costruzione della lingua scritta La ricerca educativa, anche quella delle neuroscienze, ha messo in evidenza la stretta relazione che intercorre fra alfabetizzazione emergente e successivo apprendimento di lettura e scrittura. Una verifica tempestiva delle abilità simboliche e linguistiche è imprescindibile per accompagnare lo sviluppo e per predisporre strategie di recupero delle carenze riscontrate, nel caso si individuino segnali precoci di difficoltà. In alcune scuole dell'infanzia della provincia di Palermo è stato realizzato un laboratorio della durata di 45 ore, secondo una precisa impostazione metodologica, con un duplice scopo: a) sviluppare le aree emergenti dell'alfabetizzazione in età prescolare; b) fornire agli insegnanti un orientamento oggettivo per rilevare l'idoneità all'apprendimento di lettura e scrittura. L'indagine ha preso in considerazione le competenze fonologica, lessicale e pragmatica. Si è verificato se un curricolo integrato, basato sul racconto di storie, potesse migliorare la capacità di costruzione della lingua orale e scritta e la consapevolezza fonologica nei bambini di cinque anni di età. Pur rimanendo su un piano empirico, gli esiti dell'indagine mostrano che il percorso didattico ha prodotto un sensibile miglioramento delle prestazioni dei soggetti.